(untitled) (Malay Literature, 2024)
Mirror for rulers’ genre is a part of the history of traditional Malay literature, providing guidance and advice to rulers on effective governance. This genre of writing typically contains didactic historical narratives suhlm.rted by quotations from the Quran, hadith, or specific sayings by Islamic scholars, aimed at leaving a lasting impression on readers, particularly the kings or the dignitaries. In the early 20th century, this tradition was carried on by Raja Ali Kelana through the production of Kitab Kumpulan Ringkas Berbetulan Lekas, which features additional historical elements, specifically the genealogical lineage of the Bugis royal family within the Riau-Lingga Sultanate. Consequently, this study focuses on analysing the historical elements within the Kitab Kumpulan Ringkas Berbetulan Lekas, with particular attention to the genealogical lineage of the Bugis monarchs. This research employs a qualitative ahlm.oach, utilising content analysis method with an inductive ahlm.oach. The findings of the study indicate that this literary work features elements of patriotism, specifically regarding the sources of power of the Bugis kings within the Riau-Lingga Sultanate, the lineage of the Bugis kings who inherited the position of Yang Dipertuan Muda, and the narrative of Opu Bugis as a patriot. This reflects the author’s intention to evoke a sense of patriotism in response to the socio-political pressures faced by the Riau-Lingga Sultanate due to Western colonialism. Full text: PDF